HUKUM JUAL BELI ONLINE DI BUKALAPAK PERSPEKTIF SURAT AL-BAQARAH : 275 - Muhammad Ali, Zulkarnain; Abdurrahim (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2021)
Online buying and selling is widely done by the public in some e-commerce applications, because of its ease in transacting. In classical studies, especially the 4 largest schools in the world say that buying and selling must meet the pillars of buying and selling, but what happens in online buying and selling many unfulfilled pillars, for example sellers and buyers do not meet in person at one time and place, objects of goods that cannot be seen and selected directly, and unspoken accounts, So many people are questioning this issue. This type of research is qualitative, with the collection of library research data through literature related and relevant to the title of this study. The results of this study showed that in formulating the law of buying and selling in Q.S Al-Baqarah: 275 mufassir such as Ibn Kathir, Al-Qurtubi, Al-Wasith, Al-Jashshash have a classical view that the fulfillment of the pillars of buying and selling is done traditionally (not online buying and selling) and they agree that buying and selling must be fulfilled in harmony. As for the opinion of buying and selling online in bukalapak is not unfulfilled, but does not appear physically. In its fatwa MUI allows online buying and selling, which is seen as the substance of the sale and purchase, as long as the two parties who transact are happy with each other, not unjust, and the goods sold do not contain gharar and are not prohibited goods in Islam.